Membrane electrode, preparation method thereof and fuel cell

By regulating the PA doping amount of the catalytic layer and the proton exchange membrane in the membrane electrode of HT-PEMFC, the problems of power density and PA management of ultra-thin films and low-load Pt fuel cells are solved, and the power density and stability of fuel cells are improved are achieved.

CN119560598APending Publication Date: 2025-03-04SHANGHAI INST OF SPACE POWER SOURCES
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411682309.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

High-temperature proton exchange membrane fuel cell (HT-PEMFC) with ultra-thin films and low load Pt has challenges in power density and PA management, resulting in lower power density and deterioration in performance.

Method used

By macro-regulating the doping amount of phosphoric acid (PA) in the catalytic layer and the proton exchange membrane of the membrane electrode, forming an acid-enhancing catalytic layer and an acid-enhancing proton exchange membrane, ensuring the stable distribution of PA, thereby increasing the power density of the fuel cell.

Benefits of technology

The power density of the fuel cell is improved, the occurrence of "acid flooding" phenomenon is reduced, the proton conductivity of the proton exchange membrane and the Pt utilization rate of the catalytic layer are ensured, and the stability of the fuel cell is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560598A_ABST
    Figure CN119560598A_ABST
Patent Text Reader

Abstract

The invention discloses a membrane electrode, a preparation method thereof and a fuel cell, the membrane electrode comprises a catalyst layer and a proton exchange membrane, the catalyst layer comprises an anode catalyst layer and a cathode catalyst layer, and the anode catalyst layer and the cathode catalyst layer are respectively arranged on two sides of the proton exchange membrane; the catalyst layer and the proton exchange membrane are both doped with phosphoric acid. By macroscopically regulating and controlling the PA content of the catalyst layer and the proton exchange membrane in the membrane electrode, more three-phase reaction interfaces are constructed, so that the Pt catalyst can be fully utilized, and unnecessary migration of PA is reduced, thereby avoiding the phenomenon of acid flooding, ensuring sufficient PA in the proton exchange membrane to provide sufficient proton conductivity, and improving the proton exchange efficiency. And the power density of the fuel cell is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a membrane electrode, a preparation method thereof and a fuel cell. Background Art

[0002] Proton Exchange Membrane Fuel Cell (PEMFC) is an efficient and environmentally friendly energy conversion technology that converts chemical energy directly into electrical energy. According to the different operating temperatures, PEMFC is divided into low-temperature PEMFC (LT-PEMFC) based on Nafion membrane and high-temperature PEMFC (HT-PEMFC) based on phosphoric acid (PA)-doped polybenzimidazole (PBI) membrane. Currently, the commercially successful low-temperature PEMFC has problems such as high requirements for fuel gas purity and complex water and heat management systems, which limit its application scenarios. Therefore, HT-PEMFC with an operating temperature above 120°C has attracted much attention due to its advantages such as fast reaction kinetics (high energy efficiency), high tolerance to fuel / air impurities, simple plate design, and better heat and water management. It is expected to become the next generation of PEMFCs, specifically used in hydrogen fuel vehicles and combined heat and power (CHP) systems.

[0003] Although HT-PEMFC has many advantages, its commercialization process still faces challenges due to its low power density. The core component that determines the power density of HT-PEMFC is the membrane electrode, which consists of a catalyst layer, a proton exchange membrane, and a gas diffusion layer. At present, two methods are used in practical applications to improve the power density of fuel cells:

[0004] (1) Using a catalytic layer with a high platinum (Pt) loading to provide more active sites for electrochemical reactions, thereby increasing the power density of the fuel cell, but the use of a high content of Pt will lead to a significant increase in cost.

[0005] (2) Reduce the thickness of the proton exchange membrane to reduce the ohmic impedance of the proton exchange membrane, thereby increasing the power density of the fuel cell. However, an ultra-thin proton exchange membrane will reduce its ability to retain PA content. Therefore, during the operation of the fuel cell, when there is a difference in PA concentration between the proton exchange membrane and the catalyst layer, PA is very likely to escape from the proton exchange membrane and migrate to the catalyst layer, which significantly reduces the proton conductivity of the proton exchange membrane and greatly increases the ohmic impedance of the fuel cell, failing to achieve the effect of increasing the power density.

[0006] In order to reduce costs and increase power density at the same time, in the prior art, more and more researchers are paying attention to low-Pt-loaded HT-PEMFC with ultra-thin proton exchange membrane (hereinafter referred to as "ultra-thin membrane"). However, the catalyst layer with low Pt loading is usually thin, which also leads to a decrease in the amount of PA it can accommodate. At the same time, with the continuous migration of PA from the ultra-thin membrane during the operation of the fuel cell, the PA content in the catalyst layer close to the ultra-thin membrane side is too high and the PA content away from the ultra-thin membrane side is too low, which in turn causes local "acid flooding" phenomenon, resulting in deterioration of fuel cell performance (such as the power density of the fuel cell). The "acid flooding" phenomenon refers to excessive PA occupying the active sites of the catalyst, thereby affecting the normal progress of the electrochemical reaction.

[0007] In summary, there is a lack of effective means for PA management of HT-PEMFC with ultra-thin film and low Pt loading. Improving the power density of HT-PEMFC with ultra-thin film and low Pt loading is of great practical significance for promoting the further application of HT-PEMFC. Summary of the invention

[0008] The purpose of the present invention is to improve the power density of HT-PEMFC with ultra-thin film and low Pt loading by macro-controlling the PA doping amount of the catalyst layer and the proton exchange membrane in the membrane electrode of HT-PEMFC.

[0009] In order to achieve the above-mentioned purpose, the present invention provides a membrane electrode, comprising a catalyst layer and a proton exchange membrane, wherein the catalyst layer comprises an anode catalyst layer and a cathode catalyst layer, and the anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the proton exchange membrane; the catalyst layer and the proton exchange membrane are both doped with phosphoric acid.

[0010] Furthermore, the anode catalyst layer is doped with phosphoric acid to form an anode acid-enhancing catalyst layer, and the phosphoric acid doping amount in the anode acid-enhancing catalyst layer is 0.3 mg / cm 2 ~3mg / cm 2 .

[0011] Furthermore, the cathode catalyst layer is doped with phosphoric acid to form a cathode acid-increasing catalyst layer, and the phosphoric acid doping amount in the cathode acid-increasing catalyst layer is 0.5 mg / cm 2 ~6mg / cm 2 .

[0012] Furthermore, the anode catalyst layer and the cathode catalyst layer are doped with phosphoric acid to form an anode acid-enhancing catalyst layer and a cathode acid-enhancing catalyst layer, respectively. The total amount of phosphoric acid content in the anode acid-enhancing catalyst layer and the phosphoric acid content in the cathode acid-enhancing catalyst layer is 1 mg / cm 2 ~10mg / cm 2 The total phosphoric acid content ratio of the two is 1:(1~20).

[0013] Furthermore, the phosphoric acid doping amount in the proton exchange membrane is 250% to 450% by mass.

[0014] The present invention also provides a method for preparing the above-mentioned membrane electrode, comprising the following steps:

[0015] Step S1, mixing phosphoric acid and a polar solvent to obtain a phosphoric acid doping solution;

[0016] Step S2, using the phosphoric acid doping solution to perform phosphoric acid doping treatment on the anode catalyst layer and / or the cathode catalyst layer;

[0017] Step S3, heating and drying the anode catalyst layer and / or the cathode catalyst layer treated in step S2, and removing the polar solvent to obtain the anode acid-enhanced catalyst layer and / or the cathode acid-enhanced catalyst layer;

[0018] Step S4, soaking the proton exchange membrane in phosphoric acid for a certain period of time to obtain a phosphoric acid-doped proton exchange membrane;

[0019] Step S5, using a hot pressing method, the anode acid-enhancing catalyst layer, the phosphoric acid-doped proton exchange membrane, and the cathode acid-enhancing catalyst layer are compounded in sequence to obtain a membrane electrode.

[0020] Furthermore, the polar solvent is any one or more of ethanol, water, ether, acetone, acetic acid, and ethyl acetate.

[0021] Furthermore, in the step S1, the volume ratio of the phosphoric acid to the polar solvent is 1:6 to 1:20.

[0022] Furthermore, in the step S2, the phosphoric acid doping treatment is to use a spray gun to spray the phosphoric acid doping solution on the anode catalyst layer and / or the cathode catalyst layer.

[0023] The present invention also provides a fuel cell, characterized in that it comprises the above-mentioned membrane electrode.

[0024] Compared with the prior art, the beneficial effects of the present invention at least include:

[0025] For HT-PEMFC with ultra-thin film and low Pt loading, in the membrane electrode provided by the present invention, the PA content of the catalyst layer and the proton exchange membrane is macro-controlled, and the stable distribution of PA is maintained by the acid-enhanced catalyst layer and the proton exchange membrane, thereby realizing the improvement of the power density of the fuel cell. PA is pre-doped in the catalyst layer so that PA is evenly distributed in the catalyst layer, and it is easier to reach a concentration equilibrium state, avoiding unnecessary migration of PA. On the one hand, more three-phase reaction interfaces (solid catalyst, liquid PA, and reaction interface of gas reaction medium) are constructed in the part of the catalyst layer away from the ultra-thin film side, so that more Pt active sites are fully utilized, and at the same time, the proton transmission channel of the catalyst layer is increased, and the occurrence of electrochemical reactions is promoted. By improving the efficiency of the electrochemical reaction and increasing the consumption rate of protons, the excessive accumulation of PA as a proton carrier is avoided, and the "acid flooding" phenomenon is reduced, thereby improving the power density and stability of the fuel cell. On the other hand, the pre-PA doping method reduces the concentration difference between the proton exchange membrane and the catalytic layer, thereby reducing the concentration driving force for PA migration in the proton exchange membrane, reducing the PA loss rate in the proton exchange membrane, ensuring the proton conductivity of the proton exchange membrane, and avoiding excessive PA in the proton exchange membrane from migrating to the catalytic layer, further reducing the "acid flooding" phenomenon. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic structural diagram of the membrane electrode in the high-temperature proton exchange membrane fuel cell with ultra-thin film and low Pt loading of the present invention.

[0027] Figure 2 The membrane electrode polarization characteristic curves of Examples 1 to 3 and the comparative example under H2-Air conditions.

[0028] Figure 3 It is the membrane electrode polarization characteristic curve of Examples 1 to 3 and the comparative example under H2-O2 conditions.

[0029] Figure 4 Under H2-Air conditions, 100mA / cm 2 Membrane electrode impedance diagram of Examples 1 to 3 and the comparative example under current density.

[0030] Description of the accompanying drawings:

[0031] Proton exchange membrane 10,

[0032] Catalytic layer 20, anode catalyst layer 21, cathode catalyst layer 22,

[0033] Gas diffusion layer 30, anode gas diffusion layer 31, cathode gas diffusion layer 32, microporous layer 311 of anode gas diffusion layer, support layer 312 of anode gas diffusion layer, microporous layer 321 of cathode gas diffusion layer, support layer 322 of cathode gas diffusion layer. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0036] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0037] The “ultra-thin film” described herein refers to a proton exchange membrane having an ultra-thin thickness, and the thickness of the “ultra-thin film” is 10 μm to 20 μm.

[0038] The "gas diffusion electrode" described in this article consists of a catalyst layer and a gas diffusion layer.

[0039] As used herein, the terms "load" and "content" are used interchangeably.

[0040] In high-temperature proton exchange membrane fuel cells (HT-PEMFCs), phosphoric acid (PA) acts as the main carrier of proton transport, promoting the transfer of protons (H +) is transferred in the proton exchange membrane, the anode catalyst layer, and the cathode catalyst layer, so that the protons are transferred in the anode catalyst layer: H2→2H + +2e - , occurs in the cathode catalyst layer: O2+4H + +4e - →2H2O. The anode catalyst layer and the cathode catalyst layer include Pt catalysts, and the Pt catalysts are any one or more of Pt / C, PtFe / C or PtCo / C. The Pt loading of the anode catalyst layer is 0.2 mg / cm 2 ~0.5mg / cm 2 The Pt loading of the cathode catalyst layer is 0.1 mg / cm 2 ~0.5mg / cm 2 . In the catalytic layer, the Pt catalyst (solid), PA (liquid) and the reaction medium (oxidation or air) form three-phase reaction interfaces (Triple Phase Boundaries, TPBs), which are key areas for electrochemical reactions to occur. They provide a place for the reaction medium to be transferred to the catalyst surface and participate in the reaction. Therefore, the distribution of PA in the membrane electrode will significantly affect the construction of the effective three-phase reaction interface in the catalytic layer and the proton conduction capacity of the proton exchange membrane.

[0041] However, as described in the background art, the distribution of PA in HT-PEMFC with ultra-thin film and low Pt loading is not ideal, resulting in low power density of the fuel cell. The main reasons are:

[0042] (1) As the thickness of the ultra-thin proton exchange membrane decreases, its ability to accommodate PA decreases. Then, PA is easily lost from the proton exchange membrane to the catalyst layer under the drive of concentration difference, which leads to a significant decrease in the proton conductivity of the proton exchange membrane, increases the ohmic impedance of the battery, and causes a decrease in the power density of the fuel cell.

[0043] (2) The PA in the traditional catalyst layer without acid supplementation mainly comes from the migration of PA in the proton exchange membrane driven by concentration difference. However, the catalyst layer with low Pt loading is thinner. The thinning of the catalyst layer reduces its ability to accommodate PA, and it is very easy for the PA content near the proton exchange membrane to be too high in the catalyst layer. As a result, part of the catalyst layer near the proton exchange membrane is prone to "acid flooding", which hinders the reaction medium (oxygen or air) from reaching the catalyst surface, affecting the normal progress of the electrochemical reaction, and thus causing the power density of the fuel cell to decrease.

[0044] It can be seen that regulating the reasonable distribution of PA in the membrane electrode is very necessary to ensure the power density of ultra-thin film and low-load Pt fuel cells.

[0045] To solve the above problems, the present invention proposes a membrane electrode with a reasonable PA distribution for a high-temperature proton exchange membrane fuel cell with an ultra-thin film and a low Pt loading. By precisely controlling the PA content in the proton exchange membrane, the cathode catalyst layer, and the anode catalyst layer, the PA is reasonably distributed in various parts of the membrane electrode, thereby ensuring that the proton exchange membrane has sufficient proton conduction capacity. At the same time, the additional PA added in the catalyst layer is used to construct more three-phase reaction interfaces, thereby improving the utilization rate of Pt, promoting the occurrence of electrochemical reactions, and ensuring the power density of the fuel cell.

[0046] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0047] The present invention provides a membrane electrode for HT-PEMFC with ultra-thin film and low Pt loading, the structural schematic diagram of which is shown in FIG. Figure 1 As shown. The membrane electrode is composed of a proton exchange membrane 10, a catalyst layer 20, and a gas diffusion layer 30 that are tightly combined with each other; wherein the catalyst layer 20 includes an anode catalyst layer 21 and a cathode catalyst layer 22; and the gas diffusion layer 30 includes an anode gas diffusion layer 31 and a cathode gas diffusion layer 32. The proton exchange membrane 10 is located in the middle of the membrane electrode, and its main function is to conduct protons. The anode catalyst layer 21 and the cathode catalyst layer 22 are respectively located on both sides of the proton exchange membrane 10, and are used to provide active sites for electrochemical reactions. The anode catalyst layer 21 is used for the oxidation reaction of hydrogen, and the cathode catalyst layer 22 is used for the reduction reaction of oxygen. The anode gas diffusion layer 31 and the cathode gas diffusion layer 32 are respectively located on the surfaces of the anode catalyst layer 21 and the cathode catalyst layer 22 away from the proton exchange membrane 10, and are used to provide a transmission channel for the reaction gas, support the catalyst layer 20, conduct electrons, and help discharge the generated water. The gas diffusion layer 30 includes support layers 312, 322 and microporous layers 311, 321; wherein the support layers 312, 322 are carbon paper and / or carbon cloth, and the microporous layers 311, 321 include carbon powder and polytetrafluoroethylene (PTFE), and the carbon powder is at least one of activated carbon, graphitized carbon, carbon nanotubes, carbon nanobelts, and carbon nanospheres.

[0048] The membrane electrode provided by the present invention performs phosphoric acid doping on at least one of the anode catalyst layer 21 and the cathode catalyst layer 22 contained in the membrane electrode to form an anode acid-enhanced catalyst layer and / or a cathode acid-enhanced catalyst layer. The catalyst layer 20 with low Pt loading is usually of low thickness, which reduces the PA accommodating capacity of the catalyst layer 20, resulting in that in the catalyst layer 20 near the proton exchange membrane 10 side, after the PA content reaches a certain level, the PA from the proton exchange membrane 10 is not easy to migrate into the catalyst layer, and the PA is very easy to be blocked on the surface of the catalyst layer 20 near the proton exchange membrane 10 side, and the part of the catalyst layer 20 far from the proton exchange membrane 10 side even has a very low PA content due to the continuous outward migration of PA. Therefore, in some embodiments, a certain amount of PA is pre-doped into the anode catalyst layer 21 and / or the cathode catalyst layer 22. On the one hand, it helps to build more effective three-phase reaction interfaces, increase the proton transmission channel of the catalyst layer 20, so that the Pt catalyst far from the proton exchange membrane 10 side is also utilized, and the utilization rate of Pt in the catalyst layer 20 is improved, thereby promoting the occurrence of electrochemical reactions and improving the power density of the fuel cell. At the same time, a faster reaction rate means that more protons are consumed, and the excessive accumulation of PA in the catalyst layer 20 close to the proton exchange membrane 10 is avoided, effectively preventing the local "acid flooding" phenomenon. On the other hand, pre-doping a certain amount of PA reduces the concentration difference between the catalyst layer 20 and the proton exchange membrane 10, thereby reducing the concentration driving force of PA migrating from the proton exchange membrane 10 to the catalyst layer 20, reducing the excessive loss of PA in the proton exchange membrane 10, making it easier for the PA distribution in the membrane electrode to reach the equilibrium state, thereby ensuring the proton conductivity of the proton exchange membrane 10, and further improving the power density of the fuel cell. However, too high a content of PA is likely to occupy the active sites of Pt, affecting the normal progress of the electrochemical reaction. Therefore, in some embodiments of the present invention, the PA content of the anode acidification catalyst layer is 0.5 mg / cm 2 ~3mg / cm 2 The PA content of the cathode acid-increasing catalyst layer is 0.5 mg / cm 2 ~6mg / cm 2 .

[0049] In some preferred embodiments, the anode catalyst layer 21 and the cathode catalyst layer 22 are both doped with PA to further optimize the PA distribution in the membrane electrode, construct more three-phase reaction interfaces in the catalyst layer 20, and improve the power density of the fuel cell. When the anode catalyst layer 21 and the cathode catalyst layer 22 are both doped with PA, the total amount of the PA content of the anode acid-enhanced catalyst layer and the PA content of the cathode acid-enhanced catalyst layer is 1 mg / cm 2 ~10mg / cm 2 The total ratio of PA content between the two is 1:(1~20).

[0050] The PA content of the cathode acid-enhancing catalyst layer is higher than the PA content of the anode acid-enhancing catalyst layer because the cathode catalyst layer is usually thicker than the anode catalyst layer and requires more PA content to ensure uniform distribution of PA, and during the operation of the fuel cell, the cathode catalyst layer requires more proton migration to support the oxygen reduction reaction, so a higher PA concentration is required in the cathode catalyst layer to maintain effective proton migration and reaction rate. Therefore, the PA content of the cathode acid-enhancing catalyst layer is higher.

[0051] The present invention also includes performing PA doping treatment on the proton exchange membrane 10 to increase the PA content in the proton exchange membrane 10. The reduction of the PA content in the ultra-thin proton exchange membrane 10 will reduce its conductivity, increase the ohmic impedance inside the fuel cell, and thus affect the efficiency of the fuel cell in generating electricity. In some embodiments, in order to maintain the proton conductivity of the proton exchange membrane 10, thereby ensuring that the fuel cell can maintain a low internal resistance during operation, the proton exchange membrane 10 is doped with a high content of PA to prevent the proton exchange membrane 10 from being too high due to the gradual loss of PA during operation. However, a high content of PA in the proton exchange membrane 10 will lead to a decrease in mechanical strength. Although a high content of PA can improve proton conductivity, too much PA will be adsorbed around the polymer main chain, increase the distance between polymer chains, and reduce the interaction force between the main chains, thereby causing the polymer main chain to plasticize and reduce the mechanical properties of the proton exchange membrane 10. Therefore, the PA doping level of the proton exchange membrane 10 needs to find a balance between proton conductivity and mechanical strength. In some embodiments of the present invention, the PA content in the proton exchange membrane 10 is 250% to 450% by mass.

[0052] In some preferred embodiments, the proton exchange membrane 10, the anode catalyst layer 21, and the cathode catalyst layer 22 are all doped with phosphoric acid so that the PA content in the proton exchange membrane 10, the anode catalyst layer 21, and the cathode catalyst layer 22 is reasonably distributed. On the basis of taking into account the proton conduction performance and mechanical strength of the proton exchange membrane 10, the microstructure of the catalyst layer 20 is further optimized, more three-phase reaction interfaces are constructed, and the power density of the fuel cell is improved.

[0053] The present invention also provides a method for preparing the above-mentioned membrane electrode, comprising the following steps:

[0054] Step S1, mixing phosphoric acid with a polar solvent to obtain a phosphoric acid doping solution. The polar solvent includes but is not limited to water, ethanol, ether, acetone, acetic acid, and ethyl acetate. In some embodiments, the polar solvent is ethanol. In the phosphoric acid doping solution, the volume ratio of phosphoric acid to ethanol is 1:6 to 1:20. This ratio is conducive to the formation of a uniform atomization effect of the PA doping solution during the spraying process, thereby promoting the full dispersion and uniform penetration of PA in the catalytic layer, which is conducive to the uniform distribution of PA in the subsequently formed anode acid-enhanced catalytic layer and cathode acid-enhanced catalytic layer.

[0055] Step S2, using the phosphoric acid doping solution to perform phosphoric acid doping treatment on the anode catalyst layer and the cathode catalyst layer. In some embodiments, the phosphoric acid doping treatment is to spray the phosphoric acid solution on the surface of the anode catalyst layer and the cathode catalyst layer using a spray gun. The spraying helps the phosphoric acid doping solution to penetrate into the pore structure of the catalyst layer and achieve uniform penetration.

[0056] Step S3, heating and drying the anode catalyst layer and / or cathode catalyst layer treated in step S2, and removing the polar solvent to obtain the anode acid-enhanced catalyst layer and the cathode acid-enhanced catalyst layer.

[0057] Step S4, soaking the proton exchange membrane in phosphoric acid for a certain period of time to obtain a phosphoric acid-doped proton exchange membrane.

[0058] Step S5, using a hot pressing method, the anode acid-enhancing catalyst layer, the phosphoric acid-doped proton exchange membrane, and the cathode acid-enhancing catalyst layer are compounded in sequence to obtain the membrane electrode.

[0059] Unless otherwise specified, the chemicals used in the present invention are all conventional commercially available chemical reagents. These chemicals can be purchased from a number of chemical reagent suppliers and do not require special preparation or synthesis.

[0060] The present invention is further described in detail below in conjunction with specific embodiments.

[0061] Example 1

[0062] This embodiment provides a method for preparing a membrane electrode for simultaneously adjusting the PA content of a cathode catalyst layer, an anode catalyst layer, and a proton exchange membrane, the preparation method comprising: preparing a gas diffusion layer, preparing a gas diffusion electrode (Gas Diffusion Electrode, GDE), and preparing a proton exchange membrane, the GDE comprising the gas diffusion layer and the catalyst layer. The details are as follows.

[0063] (1) Preparation of gas diffusion layer: The preparation methods of the anode gas diffusion layer and the cathode diffusion layer are the same. In this embodiment, the anode gas diffusion layer and the cathode diffusion layer are both commercialized by Toray. The gas diffusion layer includes a support layer and a microporous layer.

[0064] (2) Preparation of anode acidification GDE (anode gas diffusion layer + anode acidification catalyst layer):

[0065] Step 1.1, weigh 340 mg of 30 wt.% Pt / C catalyst, add 12930 mg of deionized water to stir and wet, then add 12930 mg of anhydrous ethanol, and finally add 176 mg of 60 wt.% PTFE aqueous solution, and obtain anode catalyst slurry after ultrasonic dispersion.

[0066] Step 1.2, the anode catalyst slurry is evenly coated on the microporous layer surface of the anode gas diffusion layer by pneumatic spraying, an anode catalyst layer is generated on the microporous layer surface of the anode gas diffusion layer, and the original anode GDE is obtained after drying the anode gas diffusion layer and the anode catalyst layer.

[0067] Step 1.3, using a spray gun, uniformly spray a PA solution uniformly mixed with PA and ethanol in a volume ratio of 1:16 from the surface of the anode catalyst layer away from the anode gas diffusion layer, and PA uniformly penetrates inside the anode catalyst layer, so that the anode catalyst layer forms an anode acidification catalyst layer, and then dries at 120°C for 10 minutes, and weighs to determine the PA loading. Repeat step 1.3 until an anode acidification GDE with a suitable PA loading is obtained.

[0068] The prepared anode acidification GDE includes an anode gas diffusion layer and an anode acidification catalyst layer. The anode acidification catalyst layer includes 30% by mass of Pt / C catalyst and 20% by mass of PTFE. The Pt loading in the anode acidification catalyst layer is 0.3 mg / cm 2 , PA loading is 0.4 mg / cm 2 .

[0069] (3) Preparation of cathode acid-enhanced GDE (cathode gas diffusion layer + cathode acid-enhanced catalyst layer):

[0070] Step 2.1, weigh 175 mg of 40 wt.% PtCo / C catalyst, add 6630 mg of deionized water to stir and wet, then add 6630 mg of anhydrous ethanol, and finally add 90 mg of 60 wt.% PTFE aqueous solution, and obtain cathode catalyst slurry after ultrasonic dispersion.

[0071] Step 2.2, the cathode catalyst slurry is evenly coated on the microporous layer surface of the cathode gas diffusion layer by pneumatic spraying, a cathode catalyst layer is generated on the microporous layer surface of the cathode gas diffusion layer, and the cathode gas diffusion layer and the cathode catalyst layer are dried to obtain the original cathode GDE.

[0072] Step 2.3, using a spray gun, evenly spray the PA solution uniformly mixed in a volume ratio of 1:16 from the surface of the cathode catalyst layer away from the cathode gas diffusion layer, and uniformly penetrate the inside of the cathode catalyst layer to form a cathode acid-enhanced catalyst layer. Then, dry it at 120°C for 10 minutes, weigh to determine the PA loading, and repeat step 2.3 until a cathode acid-enhanced GDE with a suitable PA loading is obtained.

[0073] The prepared cathode acid-enhanced GDE includes a cathode gas diffusion layer and a cathode acid-enhanced catalytic layer. The cathode acid-enhanced catalytic layer includes 40% by mass of PtCo / C catalyst and 20% by mass of PTFE. The Pt loading in the cathode acid-enhanced catalytic layer is 0.2 mg / cm 2 , PA loading is 2.0 mg / cm 2 .

[0074] (4) Preparation of acid-enhanced proton exchange membrane: The acid-enhanced proton exchange membrane is prepared by an impregnation method.

[0075] Step 3.1, cutting the polybenzimidazole (PBI) film into a certain size as required.

[0076] Step 3.2, placing the cut PBI membrane in 85 wt. % phosphoric acid and soaking it at 150° C. for 2 hours.

[0077] Step 3.3, use filter paper to absorb the excess phosphoric acid on the surface of the PBI membrane, and quickly weigh it to obtain the phosphoric acid adsorption amount of the PBI membrane. The phosphoric acid adsorption amount of the PBI membrane is investigated by the mass ratio of the PBI membrane with the mass of the phosphoric acid adsorbed to the mass ratio of the original PBI membrane. Repeat steps 3.2→3.3 until the mass percentage of the phosphoric acid adsorption amount of the PBI membrane reaches 400%.

[0078] (5) Preparation of membrane electrode:

[0079] The anode acid-enhanced GDE, acid-enhanced proton exchange membrane, and cathode acid-enhanced GDE prepared above are stacked in sequence in a mold, and then the mold is placed in a hot press to perform hot pressing and molding of the membrane electrode to obtain the membrane electrode.

[0080] In this embodiment, the active area of ​​the membrane electrode prepared is 4 cm 2In the membrane electrode, the mass percentage of the PA content of the acid-enhanced proton exchange membrane is 400%, and the PA loading of the anode acid-enhanced GDE is 0.4 mg / cm 2 The PA loading of the cathode acid-enhanced GDE is 2.0 mg / cm 2 The PA loading ratio of the anode acid-enhanced GDE and the cathode acid-enhanced GDE is 1:5.

[0081] Example 2

[0082] The difference between this example and Example 1 is that in the preparation of the membrane electrode of this comparative example, the cathode GDE is not treated with phosphoric acid doping, that is, step 2.3 is not performed. In the membrane electrode prepared in this example, the PA loading of the anode acidified GDE is 1.66 mg / cm 2 , the PA loading of cathode acid-enhanced GDE is 0.

[0083] Example 3

[0084] The difference between this example and Example 1 is that in the preparation of the membrane electrode in this comparative example, the anode GDE was not subjected to phosphoric acid doping treatment, that is, step 1.3 was not performed. In the membrane electrode prepared in this example, the PA loading of the anode GDE was 0, and the PA loading of the cathode acid-enhanced GDE was 2.06 mg / cm 2 .

[0085] Comparative Example

[0086] The difference between this comparative example and Example 1 is that in the preparation of the membrane electrode in this comparative example, neither the anode GDE nor the cathode GDE is subjected to phosphoric acid doping treatment, that is, the steps 1.3 and 2.3 are not performed. In the membrane electrode prepared in this comparative example, the PA loading of the anode GDE is 0, and the PA loading of the cathode GDE is 0.

[0087] Performance testing:

[0088] Referring to GB / T 20042.5-2009, the membrane electrodes obtained in Examples 1 to 3 and the comparative example were made into fuel cells for polarization curve testing. The specific operating conditions were: the single cell operating temperature was 160°C, the anode was fed with pure hydrogen, and the cathode was fed with atmospheric pressure air or atmospheric pressure oxygen. When the cathode was fed with air, the stoichiometric ratios of the cathode feed and the anode feed were 3 and 1.5 respectively; when the cathode was fed with oxygen, the stoichiometric ratios of the cathode feed and the anode feed were 3 and 6 respectively.

[0089] Referring to GB / T 20042.5-2009, the membrane electrodes obtained in Examples 1 to 3 and the comparative example were made into fuel cells for impedance detection. The specific operating conditions were: the single cell operating temperature was 160°C, the anode was fed with pure hydrogen, the cathode was fed with atmospheric pressure air or oxygen, and the discharge current density was 0.1 A / cm 2 Or 0.5A / cm 2 .

[0090] Test results such as Figures 2 to 4 As shown. Among them, A-PA-0.40 and C-PA-2.00 represent Example 1, A-PA-1.66 and C-PA-0 represent Example 2, A-PA-0 and C-PA-2.06 represent Example 3, and A-PA-0 and C-PA-0 represent comparative examples. As an example, A-PA-0.40 represents that the PA loading of the anode acidified GDE is 0.40 mg / cm 2 , C-PA-2.00 means the PA loading of cathode acidification GDE is 2.00 mg / cm 2 .

[0091] See also Figure 2 The polarization characteristic curves of the membrane electrodes of Examples 1 to 3 of the present invention and the comparative example were measured under the condition of H2-Air (pure hydrogen is fed to the anode and air is fed to the cathode). Figure 2 It can be seen that at 0.1A / cm 2 Under the conditions of 0.602V, 0.549V, 0.589V and 0.398V, the voltages of the membrane electrodes of Examples 1 to 3 of the present invention and the comparative example are measured. The higher the voltage of the membrane electrode, the smaller the loss of membrane electrode polarization, which is beneficial to improve the power density of the fuel cell. The maximum power density of the membrane electrodes of Examples 1 to 3 of the present invention and the comparative example is measured to be 0.275W / cm 2 、0.137W / cm 2 、0.219W / cm 2 and 0.042W / cm 2 Compared with the membrane electrode of the comparative example, the power density of the membrane electrode of Example 1 of the present invention is increased by 6.55 times, which proves that the PA doping treatment of the anode catalyst layer and / or the cathode catalyst layer of the present invention can increase an effective three-phase reaction interface inside the anode catalyst layer and / or the cathode catalyst layer, improve the utilization rate of the Pt catalyst, thereby promoting the electrochemical reaction, and make it easier for the PA distribution inside the fuel cell to reach a balanced state, avoid excessive migration of PA in the proton exchange membrane, effectively maintain the proton conductivity of the proton exchange membrane, and improve the power density of the fuel cell.

[0092] See also Figure 3The polarization characteristic curves of the membrane electrodes of Examples 1 to 3 of the present invention and the comparative example were measured under the condition of H2-O2 (pure hydrogen was fed to the anode and oxygen was fed to the cathode). Figure 3 It can be seen that at 0.1A / cm 2 Under the conditions of 0.686V, 0.661V, 0.657V and 0.475V, respectively, the voltages of the membrane electrodes of Examples 1 to 3 of the present invention and the comparative example are measured; the maximum power densities of the membrane electrodes of Examples 1 to 3 of the present invention and the comparative example are measured to be 0.394W / cm 2 , 0.333W / cm 2 , 0.306W / cm 2 and 0.066W / cm 2 . Compared with the membrane electrode of the comparative example, the power density of the membrane electrode of Example 1 of the present invention is increased by 5.97 times, which also proves that the present invention effectively ensures the proton conductivity of the proton exchange membrane and constructs more three-phase reaction interfaces in the anode catalyst layer and / or the cathode catalyst layer by reasonably adjusting the PA content of different components in the membrane electrode, thereby effectively improving the power density of the fuel cell. The voltage and power density of the membrane electrode under H2-O2 conditions are higher than those under H2-Air conditions, mainly because the influence of mass transfer resistance under H2-O2 conditions is weakened, and the reaction medium can be more effectively transferred to the membrane electrode surface to participate in the reaction, thereby improving the power density of the fuel cell.

[0093] See also Figure 4 , the horizontal axis in the figure represents the real part of the impedance, and the vertical axis represents the imaginary part of the impedance. It can be seen that compared with the comparative example, the impedance of Examples 1 to 3 in the high, medium and low frequency regions of the impedance spectrum are significantly reduced. Figure 4 It can be clearly demonstrated that by using the membrane electrode of Example 1 of the present invention, the ohmic impedance and the anode-cathode charge transfer impedance of the fuel cell are significantly reduced. This is mainly because the loss rate of the PA content in the proton exchange membrane is reduced, thereby maintaining the low ohmic impedance of the proton exchange membrane. At the same time, more effective three-phase reaction interfaces are constructed in the PA-doped catalyst layer, thereby reducing the charge transfer barrier at the three-phase reaction interface of the catalyst layer, thereby achieving an increase in the power density of the fuel cell.

[0094] In summary, the membrane electrode, preparation method thereof and fuel cell provided by the present invention successfully enable the high-temperature proton exchange membrane fuel cell with ultra-thin film and low Pt loading to achieve stable operation with high power density. The present invention constructs more three-phase reaction interfaces and reduces the concentration difference between the components by macro-controlling the PA content of different components in the membrane electrode, thereby avoiding the occurrence of "acid flooding" caused by excessive PA migration blocking the pores of the catalyst layer, and at the same time ensuring sufficient PA to provide sufficient proton conductivity to improve the power density of the fuel cell. For high-temperature proton exchange membrane fuel cells with ultra-thin film and low Pt loading, the membrane electrode with reasonable distribution of PA provided by the present invention not only improves the performance of the membrane electrode, but also provides a feasible solution for reducing the use of Pt and promoting the commercialization process of HT-PEMFC, which has important practical value and industrial application prospects.

[0095] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A membrane electrode, characterized in that: It comprises a catalyst layer and a proton exchange membrane. The catalyst layer comprises an anode catalyst layer and a cathode catalyst layer. The anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the proton exchange membrane. The catalyst layer and the proton exchange membrane are both doped with phosphoric acid.

2. The membrane electrode according to claim 1, characterized in that The anode catalyst layer is doped with phosphoric acid to form an anode acid-increasing catalyst layer, and the phosphoric acid doping amount in the anode acid-increasing catalyst layer is 0.3 mg / cm 2 ~3mg / cm 2 .

3. The membrane electrode according to claim 1, characterized in that The cathode catalyst layer is doped with phosphoric acid to form a cathode acid-increasing catalyst layer, and the phosphoric acid doping amount in the cathode acid-increasing catalyst layer is 0.5 mg / cm 2 ~6mg / cm 2 .

4. The membrane electrode according to claim 1, characterized in that The anode catalyst layer and the cathode catalyst layer are doped with phosphoric acid to form an anode acid-enhancing catalyst layer and a cathode acid-enhancing catalyst layer, respectively. The total amount of phosphoric acid content in the anode acid-enhancing catalyst layer and the phosphoric acid content in the cathode acid-enhancing catalyst layer is 1 mg / cm 2 ~10mg / cm 2 The total phosphoric acid content ratio of the two is 1:(1~20).

5. The membrane electrode according to claim 1, characterized in that The phosphoric acid doping amount in the proton exchange membrane is 250% to 450% by mass.

6. A method for preparing a membrane electrode as claimed in any one of claims 1 to 5, characterized in that: The steps include: Step S1, mixing phosphoric acid and a polar solvent to obtain a phosphoric acid doping solution; Step S2, using the phosphoric acid doping solution to perform phosphoric acid doping treatment on the anode catalyst layer and / or the cathode catalyst layer; Step S3, heating and drying the anode catalyst layer and / or the cathode catalyst layer treated in step S2, and removing the polar solvent to obtain the anode acid-enhanced catalyst layer and / or the cathode acid-enhanced catalyst layer; Step S4, soaking the proton exchange membrane in phosphoric acid for a certain period of time to obtain a phosphoric acid-doped proton exchange membrane; Step S5, using a hot pressing method, the anode acid-enhancing catalyst layer, the phosphoric acid-doped proton exchange membrane, and the cathode acid-enhancing catalyst layer are compounded in sequence to obtain a membrane electrode.

7. The method for preparing a membrane electrode according to claim 6, characterized in that: The polar solvent is any one or more of ethanol, water, ether, acetone, acetic acid, and ethyl acetate.

8. The method for preparing a membrane electrode according to claim 6, characterized in that: In the step S1, the volume ratio of the phosphoric acid to the polar solvent is 1:6 to 1:

20.

9. The method for preparing a membrane electrode according to claim 6, characterized in that: In the step S2, the phosphoric acid doping treatment is to use a spray gun to spray the phosphoric acid doping solution on the anode catalyst layer and / or the cathode catalyst layer.

10. A fuel cell, characterized in that: Comprising the membrane electrode as claimed in claim 1.

Citation Information

Cited By

  • Method for constructing interface of high-performance ionic membrane and catalyst layer

    CN120565744A

  • Membrane electrode, preparation method thereof and high-temperature proton exchange membrane fuel cell

    CN120657182A